PENGARUH CSR DAN MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN DENGAN GCG SEBAGAI PEMODERASI - Ponga, Bogam Tempar; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research was to discover the effect of corporate social responsibility disclosure and intellectualcapital disclosure of the company with a value of GCG as a moderating variable on manufacturing companiesthat listed in Indonesia Stock Exchange 2010-2013. The approach that used in this research is a quantitativeapproach, it is to analyze the data in the form of numbers and perform data analysis using statistical procedures.The data used in this research was obtained from the Annual Report of the manufacturing company. Afterpassing through the stage of purposive sampling, so the samples that fit is as many as 27 companies. Dataanalysis techniques in this study using classic assumption test and multiple linear regression analysis usingSPSS20.The results ofthis research showed that CSR disclosure variables affect the value of the company, theintellectual capital disclosure does not affect the value of the company. While CSR moderated by GCG does notaffect the value of the company and intellectual capital disclosure that is moderated by GCG effect on the value ofthe company.Keywords: Corporate Social Responsibility Disclosure, Intellectual capital disclosure, Good CorporateGovernance, Corporate Values.